Schematic models for active nonlinear microrheology - Gnann, Manuel Victor; Gazuz, Igor; Puertas, Antonio Manuel; Fuchs, Matthias; Voigtmann, Thomas (My University, 2011)
We analyze the nonlinear active microrheology of dense colloidal suspensions using a schematic model of mode-coupling theory. The model describes the strongly nonlinear behavior of the microscopic friction coefficient as a function of applied external force in terms of a delocalization transition. To probe this regime, we have performed Brownian dynamics simulations of a system of quasi-hard spheres. We also analyze experimental data on hard-sphere-like colloidal suspensions [Habdas et al., Europhys. Lett., 2004, 67, 477]. The behavior at very large forces is addressed specifically.
Keywords: 530